2019
DOI: 10.1371/journal.pone.0226163
|View full text |Cite
|
Sign up to set email alerts
|

PTH1-34 improves bone healing by promoting angiogenesis and facilitating MSCs migration and differentiation in a stabilized fracture mouse model

Abstract: ObjectivePTH1-34 (parathyroid hormone 1–34) is the only clinical drug to promote osteogenesis. MSCs (mesenchymal stem cells) have multidirectional differentiation potential and are closely related to fracture healing. This study was to explore the effects of PTH1-34 on proliferation and differentiation of endothelial cells and MSCs in vitro, and on angiogenesis, and MSCs migration during fracture healing in vivo.MethodsMice with stabilized fracture were assigned to 4 groups: CON, PTH (PTH1-34 40 μg/kg/day), MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…In the network, the orange points represented the candidates, the yellow points presented the therapeutic targets with weak linkage to osteogenesis and the huge green points stood for the core targets, being defined based on existing studies and data. Runt-related transcription factor 2 (RUNX-2), vascular endothelial grow factor (VEGF), fibroblast growth factor receptor 2 (FGFR2) and CD31 (platelet/endothelial cell adhesion molecule) had biological function of coupling osteogenic differentiation with angiogenesis( Kawane et al, 2018 ; Qiao et al, 2018 ; Jiang et al, 2019 ). Semaphorin 3A played an essential role in regulating the osteogenic differentiation to promote bone regeneration( Zhang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the network, the orange points represented the candidates, the yellow points presented the therapeutic targets with weak linkage to osteogenesis and the huge green points stood for the core targets, being defined based on existing studies and data. Runt-related transcription factor 2 (RUNX-2), vascular endothelial grow factor (VEGF), fibroblast growth factor receptor 2 (FGFR2) and CD31 (platelet/endothelial cell adhesion molecule) had biological function of coupling osteogenic differentiation with angiogenesis( Kawane et al, 2018 ; Qiao et al, 2018 ; Jiang et al, 2019 ). Semaphorin 3A played an essential role in regulating the osteogenic differentiation to promote bone regeneration( Zhang et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…BMSCs circulate throughout the body after intravenous administration, the administered BMSCs are mostly retained in the lungs, and the homing rate to fractures is 1-2%. In this study, we demonstrated that DPSCs fluorescently stained with PKH26 and transplanted were localized in the fracture site [31,32]. Moreover, transplanted DPSCs stained with PKH26 showed mature osteoblasts by SP7 expression.…”
Section: Discussionmentioning
confidence: 64%
“…However, combination treatment in systemic applying of MSCs for bone engineering is a less explored area of research. Most of researches focus on protein molecule or ultrasound which could promote the effects on the angiogenesis efficiency of MSCs, such as erythropoietin (EPO) [ 38 ], LIPUS [ 49 ], and PTH1-34 [ 55 ]; some combination treatments could have a direct effect on osteogenesis, such as IGF-I [ 58 ] and BMP2 [ 45 ]; some protein molecules could increase the homing of transplanted MSCs to bone, such as LLP2A-Ale [ 43 , 52 ] and PTH1-34 [ 55 ]. Besides, hypoxic was detected to be an effective way to improve the survival rate, recruitment, and osteogenesis of MSCs in transplantation, and its effects were mainly achieved through the SDF-1/CXCR4 axis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%